2002
DOI: 10.1016/s0074-7696(02)19014-0
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and nonconventional roles of the nucleolus

Abstract: As the most prominent of subnuclear structures, the nucleolus has a well-established role in ribosomal subunit assembly. Additional nucleolar functions, not related to ribosome biogenesis, have been discovered within the last decade. Built around multiple copies of the genes for preribosomal RNA (rDNA), nucleolar structure is largely dependent on the process of ribosome assembly. The nucleolus is disassembled during mitosis at which time preribosomal RNA transcription and processing are suppressed; it is reass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(144 citation statements)
references
References 298 publications
3
135
1
2
Order By: Relevance
“…1996; Dillon and Festenstein, 2002;Olson et al, 2002;Garagna et al, 2004). Examination of the immunostaining for heterochromatin marker H4K20m (Schotta et al, 2004) in acinar HMECs, both in 3D culture and on sections of normal breast tissue, indicated that the perinucleolar concentration of heterochromatin is also a trait of the differentiation of HMECs ( Figure 4B).…”
Section: Molecular Biology Of the Cell 352mentioning
confidence: 96%
“…1996; Dillon and Festenstein, 2002;Olson et al, 2002;Garagna et al, 2004). Examination of the immunostaining for heterochromatin marker H4K20m (Schotta et al, 2004) in acinar HMECs, both in 3D culture and on sections of normal breast tissue, indicated that the perinucleolar concentration of heterochromatin is also a trait of the differentiation of HMECs ( Figure 4B).…”
Section: Molecular Biology Of the Cell 352mentioning
confidence: 96%
“…The components of higher order nuclear architecture, including nuclear pores [22], the nuclear matrix, and subnuclear domains, contribute to the subnuclear distribution and activities of genes and regulatory factors [21,23]. Compartmentalization of regulatory complexes is illustrated by focal organization of PML bodies [24], Runx bodies [25,26], the nucleolus [27], and chromosomes [28], as well as by the punctate intranuclear distribution of sites for replication [29], DNA repair [30], transcription [31], and the processing of gene transcripts [32][33][34]. There is emerging recognition that nuclear structure and function are casually related.…”
Section: Vitamin D-mediated Gene Expression Within the Three Dimensiomentioning
confidence: 99%
“…Thus, many non-traditional functions of the nucleolus have been proposed [5][6][7]9]. These include signal recognition particle assembly, small RNA modification, RNA editing, telomerase maturation, nuclear export, cell cycle control, and stress sensor [17][18][19][20][21][22]. The nucleolar proteins unrelated to ribosome assembly mostly contain an RNA-binding motif or have a chaperone function.…”
Section: Plurifunctionality Of the Nucleolusmentioning
confidence: 99%